Camera Trapping And Conservation In Lanjak Entimau Wildlife Sanctuary, Sarawak, Borneo - J., Mohd Azlan; Engkamat, L. (2013)
Information on the distribution of species is important in prescribing sound management practices for a protected area. In view of this, we conducted a series of camera trapping surveys in Lanjak Entimau Wildlife Sanctuary, Sarawak, Malaysian Borneo. A total of 20 camera traps was deployed primarily in riverine forests over two sampling periods (2003 and 2006) spanning 10 months altogether. A total of 1945 camera trap days yielded 537 of photographs of at least 21 species of mammals and ﬁ ve species of birds. Of these, four mammalian species are endemic to Borneo and two species are listed as endangered by the IUCN. In addition, our camera trapping survey has provided more detailed information on activity patterns of some cryptic mammal species. Finally, we discuss potential threats to selected mammal species in this area and suggest possible mitigation measures. We emphasize that regular monitoring of wildlife in protected areas should not be neglected, especially when biodiversity in this region is experiencing accelerated and unprecedented rates of extinction.